Podocin is translocated to cytoplasm in puromycin aminonucleoside nephrosis rats and in poor-prognosis patients with IgA nephropathy - Fukuda, Hiromitsu (Cell Tissue Res, 2015)
Podocytes serve as the final barrier to urinary protein loss through a highly specialized structure called a slit membrane and maintain foot process and glomerular basement membranes. Podocyte injury results in progressive glomerular damage and accelerates sclerotic changes, although the exact mechanism of podocyte injury is still obscure. We focus on the staining gap (podocin gap) defined as the staining difference between podocin and synaptopodin, which are normally located in the foot process. In puromycin aminonucleoside nephrosis rats, the podocin gap is significantly increased (p < 0.05) and podocin is translocated to the cytoplasm on days 7 and 14 but not on day 28. Surprisingly, the gap is also significantly increased (p < 0.05) in human kidney biopsy specimens of poor-prognosis IgA nephropathy patients. This suggests that the podocin gap could be a useful marker for classifying the prognosis of IgA nephropathy and indicating the translocation of podocin to the cytoplasm. Next, we find more evidence of podocin trafficking in podocytes where podocin merges with Rab5 in puromycin aminonucleoside nephrosis rats at day 14. In immunoelectron microscopy, the podocin positive area was significantly translocated from the foot process areas to the cytoplasm (p< 0.05) on days 7 and 14 in puromycin aminonucleoside nephrosis rats. Interestingly, podocin is also translocated to the cytoplasm in poor-prognosis human IgA nephropathy. In this paper, we demonstrate that the translocation of podocin by endocytosis could be a key traffic event of critical podocyte injury and that the podocin gap could indicate the prognosis of IgA nephropathy.